Technique of denominalization in client-centtred psychotherapy - Kocharian, Alexandr S.; Barinova, Natalia V. (Psychological Counseling and Psychotherapy, 2019)
The article examines the quality of the course of the psychotherapeutic process at different levels of the client’s mental organization. It is shown that the experiences of a client with a low level of mental organization become incomprehensible to the psychotherapist, and the client becomes inaccessible. There is a tendency for the psychotherapist to avoid direct contact with the client’s experiences, replacing emotional empathy with “knowledge” - “empathic knowledge”, “knowledgeable understanding”, and “sympathetic knowledge”. Such intellectual representation of the psychotherapist in contact can be useful both for the psychotherapist and for the client. At the same time, it results in the avoidance of direct emotional contact, which leads away from understanding the psychotherapeutic contact by C. Rogers. The denomination technique allows to clear the experience from the intellectual "husk" and get a pure living experience. This can happen in “body-experience-memory” space. The place the denominalization should be started depends on the characteristics of the organization of the client’s psyche. Activation of one component of the specified space eventually leads to activation of the other. These components are the elements of the "emotional scheme." Three variants of denomination are described: 1) instructing - carrying a client into depth of experiences; 2) focusing - helping a client to enter the closed experiences; 3) support. The latter option is more specific for lower organized structures of the psyche. An important condition for the work of the psychotherapist against client’s protective function of intellectualization is actualization of the organismic tendency, otherwise the likelihood of retraumatization of the client is high.